Globalizing sport : national rivalry and international community in the 1930s - Keys, Barbara J. (Harvard historical studies, 2006)
"In this book, Barbara Keys offers the first major study of the political and cultural ramifications of international sports competitions in the decades before World War II. She examines the transformation of events like the Olympic Games and the World Cup from relatively small-scale events to the celebrity-packed, politically resonant, globally popular entertainment extravaganzas familiar to us today. Focusing on the United States, Nazi Germany, and the Soviet Union, she details how countries of widely varying ideologies were drawn to participate in the emerging global culture."--Jacket.